EXPERIMENTAL INVESTIGATION ON DURABILITY OF GEOPOLYMER MORTAR USING QUARRY DUST AS FINE AGGREGATE UNDER SODIUM SULFATE AND MAGNESIUM SULFATE ATTACKS - Sinthaworn, Suppachai; Thammarat, Nathaneegan; Loedkiadtikul, Saranyu; Paijitvijarn, Pattarapon (Srinakharinwirot University Journal of Sciences and Technology, 2022)
Durability of controlled flow geopolymer (ranged 110 ± 5% by adding water) mortar which contains fly-ash, sodium hydroxide (NaOH) and sodium silicate (Na2SiO3) as a binder and use quarry dust as fine aggregate were compared to the control conventional cement mortar (W/C=0.4). From the results, the compressive strength of geopolymer mortars at the age of 28 days were in the range of 427-514 ksc, while compressive strength of geopolymer mortars (70% fly-ash with 10M NaOH) were in the range of 270-275 ksc. In exposed to sulfate solutions (5% by weight of Na2SO4 or MgSO4), compressive strength of all mixtures had increased by 34-145 ksc until 28 days but the compressive strength of geopolymer mortar 70FA[10M](S) (70% fly-ash and 10M NaOH with sand,) had reduced by 4-11 ksc. Between 28 and 56 days in sulfate solution, compressive strength of all mixtures had decreased roughly 5-50 ksc. and all of geopolymer mortar loss compressive strength more than the control mortar. However, all geopolymer mortars show lower water penetration depth than that of the control mortar. This work found out that the geopolymer mortar 65FA[10M](D) (65% fly-ash and 10M NaOH with quarry dust) can be developed as a durable mixture which obtains low water penetration depth and slight compressive strength loss in sulfate environment.